2021
DOI: 10.1186/s12957-021-02365-5
|View full text |Cite
|
Sign up to set email alerts
|

How accurate is frozen section pathology compared to permanent pathology in detecting involved margins and lymph nodes in breast cancer?

Abstract: Background Frozen section (FS) pathology has multiple limitations, and different institutions report variable experiences with the use of FS for diagnosis of tumor involvement. We aimed to compare the FS accuracy with that of permanent pathology (gold standard) regarding marginal involvement and lymph node status using data from the largest breast cancer registry in Iran. Methods In this retrospective study, women who had both FS and permanent path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…A study done by Nunez A et al reported a lower FNR of 8.6% and a higher FPR of 11.6%, accuracy of 80%, sensitivity 49%, specificity 86%, PPV 42%, and NPV 89% [20]. In another study done by Namdar et al, the overall accuracy of IFSH was 96.61% [21]. The study conducted by Boughey et al at Mayo clinic supports the adoption of IFSH assessment by all institutions to offer cost savings [7, 22].…”
Section: Discussionmentioning
confidence: 99%
“…A study done by Nunez A et al reported a lower FNR of 8.6% and a higher FPR of 11.6%, accuracy of 80%, sensitivity 49%, specificity 86%, PPV 42%, and NPV 89% [20]. In another study done by Namdar et al, the overall accuracy of IFSH was 96.61% [21]. The study conducted by Boughey et al at Mayo clinic supports the adoption of IFSH assessment by all institutions to offer cost savings [7, 22].…”
Section: Discussionmentioning
confidence: 99%
“…Inaccurate results from frozen sections will affect the operation performed by surgeons, and false negatives from frozen margins will also be encountered in the clinic. For example, intraoperative freezing indicates that the margin is negative, whereas postoperative pathology suggests the presence of residual tumor in the margin [ 23 , 24 ]. The high sensitivity of spectral-level imaging enables the detection of potentially malignant lesions in a new and feasible manner.…”
Section: Discussionmentioning
confidence: 99%
“…2 Therefore, postoperative assessment of the histopathological sections (permanent sections), a nearly accurate biopsy method that typically takes a few days, is a routine practice in distinguishing BC from adjacent normal tissue. 3 If the margin is found positive, another round of surgery is often recommended, delaying the subsequent therapy and increasing the risk of cancer recurrence or infection in the surgical site. Therefore, this setback invites innovative tools for rapid and accurate discrimination between cancer and adjacent normal breast tissues, compatible with the intraoperative workflow.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, none of these techniques are widely adopted for limited accuracy (up to 40% error rate), slow turnaround time, and subjective interpretation . Therefore, postoperative assessment of the histopathological sections (permanent sections), a nearly accurate biopsy method that typically takes a few days, is a routine practice in distinguishing BC from adjacent normal tissue . If the margin is found positive, another round of surgery is often recommended, delaying the subsequent therapy and increasing the risk of cancer recurrence or infection in the surgical site.…”
Section: Introductionmentioning
confidence: 99%